2015
DOI: 10.1111/his.12633
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin‐2 and matrix metalloproteinase‐9 expression in high‐grade endometrial cancer and their prognostic value

Abstract: Our findings suggest that LCN-2 expression may be an important independent indicator of shorter survival in patients with high-grade endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
0
18
1
Order By: Relevance
“…A shorter overall and disease-free survival period was observed in endometrial cancer patients who expressed NGAL [80].…”
Section: Effects Of Ngal On Cancer Progressionmentioning
confidence: 94%
See 1 more Smart Citation
“…A shorter overall and disease-free survival period was observed in endometrial cancer patients who expressed NGAL [80].…”
Section: Effects Of Ngal On Cancer Progressionmentioning
confidence: 94%
“…Many transcription factors, including the estrogen and androgen receptors, regulate NGAL expression by both positive and negative mechanisms [67][68][69][70][71][72][73][74][75][76][77]. 11 NGAL is an important molecule in many different types of cancer including: breast [9,10,77], colorectal (CRC) [78,79], endometrial [80], esophageal [7,81], gastric cancer [6], liver [82][83][84], lung [85][86][87] ovarian [88], pancreatic [89,90], prostate [76,91], renal [8,92] and thyroid cancer [68]. In general, elevated NGAL expression has been associated with advanced cancer and poor prognosis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Several studies have demonstrated that Lcn2 expression is increased in the presence of acute or chronic inflammation, as well as in cancer (28,29). In addition, Lcn2 is capable of interacting with matrix metalloproteinases via the formation of complexes, and then participating in the cancer cell invasion process (30). Our previous studies showed that NGAL, coded by Lcn2, is associated with the clinical prognosis of glioma (31,32).…”
Section: Introductionmentioning
confidence: 94%
“…LCN2 expression levels are particularly high in breast, pancreas, ovarian, colorectal, thyroid, and bile duct cancer tissues and cell lines derived from these tumors [27,[29][30][31][32][33][34][35]. Table 1 summarizes various studies reporting LCN2 expression levels and LCN2 s function in several cancer types.…”
Section: Lcn2 Expression In Cancermentioning
confidence: 99%